Computational analysis of microfluidic immunomagnetic rare cell separation from a particulate blood flow - Hoshino, Kazunori (2012)
We describe a computational analysis method to evaluate the efficacy of immunomagnetic rare cell separation from non-Newtonian particulate blood flow. The core procedure proposed here is calculation of local viscosity distributions induced by red blood cell (RBC) sedimentation. Numerical calculation methods have previously been introduced to simulate particulate behavior of individual RBCs. However, due to the limitation of the computational power, those studies are typically capable of calculating only very small number (less than 100) of RBCs, and are not suitable to analyze many of practical separation methods for rare cells such as circulating tumor cells (CTCs). We introduce a sedimentation and viscosity model based on our experimental measurements. The computational field is divided into small unit control volumes, where local viscosity distribution is dynamically calculated based on the experimentally found sedimentation model. For the analysis of rare cell separation, local viscosity distribution is calculated as a function of the volume RBC rate. The direction of gravity takes an important role in such a sedimentation-involved cell separation system. We evaluated the separation efficacy with multiple design parameters including the channel design, channel operational orientations (inverted and upright) and flow rates. The results showed excellent agreements with real experiments to demonstrate the effectiveness of our computational analytical method. We demonstrated higher capture efficiency with the inverted microchannel configuration. We conclude that proper direction of blood sedimentation significantly enhances separation efficiency in microfluidic devices.